Complexes of Ibuprofen Thiazolidin-4-One Derivatives with β-Cyclodextrin: Characterization and In Vivo Release Profile and Biological Evaluation - Ioana Mirela Vasincu; Maria Apotrosoaei; Florentina Lupascu; Andreea-Teodora Iacob; Simona-Eliza Giusca; Irina-Draga Caruntu; Narcisa-Laura Marangoci; Anca Roxana Petrovici; Gabriela Dumitrita Stanciu; Bogdan-Ionel Tamba; Bianca-Stefania Profire; Alin-Viorel Focsa; et al. (Pharmaceutics, 2023)
Generally, NSAIDs are weakly soluble in water and contain both hydrophilic and hydrophobic groups. One of the most widely used NSAIDs is ibuprofen, which has a poor solubility and high permeability profile. By creating dynamic, non-covalent, water-soluble inclusion complexes, cyclodextrins (CDs) can increase the dissolution rate of low aqueous solubility drugs, operating as a drug delivery vehicle, additionally contributing significantly to the chemical stability of pharmaceuticals and to reducing drug-related irritability. In order to improve the pharmacological and pharmacokinetics profile of ibuprofen, new thiazolidin-4-one derivatives of ibuprofen (4b, 4g, 4k, 4m) were complexed with β-CD, using co-precipitation and freeze-drying. The new β-CD complexes (β-CD-4b, β-CD-4g, β-CD-4k, β-CD-4m) were characterized using scanning electronic microscopy (SEM), differential scanning calorimetry (DSC), X-ray diffraction and a phase solubility test. Using the AutoDock-VINA algorithm included in YASARA-structure software, we investigated the binding conformation of ibuprofen derivatives to β-CD and measured the binding energies. We also performed an in vivo biological evaluation of the ibuprofen derivatives and corresponding β-CD complexes, using analgesic/anti-inflammatory assays, as well as a release profile. The results support the theory that β-CD complexes (β-CD-4b, β-CD-4g, β-CD-4k, β-CD-4m) have a similar effect to ibuprofen derivatives (4b, 4g, 4k, 4m). Moreover, the β-CD complexes demonstrated a delayed release profile, which provides valuable insights into the drug-delivery area, focused on ibuprofen derivatives.